Design and application of a reflective programmable metasurface element in C Band. (February 2019) - Hou, H S; Gao, X J; Zhu, L; Xie, P; Zhang, C B
Abstract: The programmable metasurface element is able to achieve continuous controllable responses by loading controllable electronic devices. In this work, a reflective programmable element working at 5GHz is implemented with varactor diodes. By tuning the biasing DC voltage loaded on the varactor diodes, the capacitance can be changed, and then the reflected phases can be tuned. Simulated results show that the reflected phase can cover the 360° and amplitude of the reflective wave is more than 0.7. In order to verify the property of the proposed element, a reflective electronically controllable metasurface is designed based on the proposed element. The metasurface is able to steer the reflective wave from -30° to 30°. The proposed element possesses distinctive features such as simple ultrathin structure, programmable control, and subwavelength, thus exhibiting the promising prospects in agile antennas.